Low Dispositional Mindfulness Predicts Self-medication of Negative Emotion With Prescription Opioids. Issue 1 (January 2015) - Garland, Eric L.; Hanley, Adam W.; Thomas, Elizabeth A.; Knoll, Paul; Ferraro, Jeffrey
<x xml:space="preserve">Abstract</x> Objectives: Although evidence is mounting that opioids are abused to self-medicate negative emotions, little is known about the traits and factors linked to opioid self-medication. One potentially crucial psychological correlate is dispositional mindfulness. Thus, the purpose of this study was to describe the prevalence of opioid self-medication among a treatment-seeking sample of prescription opioid-dependent individuals and specifically examine the relationship between dispositional mindfulness and opioid self-medication. Methods: Participants in acute detoxification or intensive outpatient treatment for prescription opioid dependence (n = 79) were recruited from a regional hospital's addictions treatment unit for this cross-sectional study. Sociodemographic data were collected along with surveys of opioid self-medication, pain level, and dispositional mindfulness. Results: Self-medication of negative affective states with opioids was quite common, with 94.9% of individuals sampled reporting self-medication behaviors. In adjusted analyses, individuals engaging in more frequent opioid use tended to self-medicate negative emotions with opioids more often than those engaging in more intermittent opioid use (β = 0.33; P < 0.05). Importantly, irrespective of opioid use frequency and other clinical and sociodemographic covariates, dispositional mindfulness was inversely associated with opioid self-medication (β = −0.42; P < 0.001), such that less mindful individuals reported using opioids more frequently to self-medicate negative emotions. Conclusions: Self-medication of negative emotions with opioids was prevalent in this sample and related to low dispositional mindfulness. Plausibly, increasing mindfulness may decrease opioid self-medication. Addictive automaticity and emotion regulation are discussed as potential mechanisms linking low dispositional mindfulness and self-medication.